Religion and politics in the 21st century global and local reflections - Vlas, Natalia; Boari, Vasile (Newcastle upon Tyne : Cambridge Scholars Publishing, 2013)
Religion and Politics in the 21st Century is composed of a number of articles that were presented during the 2012 international conference on ""Religion and Politics in the Globalization Era"" organized by the Centre for Political Analysis in Cluj-Napoca, Romania. With careful attention given to 21st century religious resurgence and its dynamic interactions with political structures and the public sphere, the present volume captures a wide variety of perspectives on contemporary religion and p...
The relation between the romanian state and the church under pressurethe political and ideological repositioning of the romanian orthodox church in post-communism; the "social partnership" between the church and state as a field of negotiation for the public status of religion in post-communist romania
Description based upon print version of record.
Description based on print version record.
Keywords: Religion and politics -- Romania -- History -- 21st century; Romania -- Politics and government -- 2001-2009.; Romania -- Religion -- 1960.; Religion and politics -- History -- 21st century; Religion and politics -- Europe -- History -- 21st century; Religion and politics -- Islamic countries -- History -- 21st century; Religion and politics -- Romania -- History -- 21st century; POLITICAL SCIENCE / Political Process / Political Advocacy; Electronic books